SENSITIVITY OF Thalassia hemprichii EXTRACT ON THE GROWTH OF PATHOGENIC BACTERIA (Vibrio alginolyticus and Aeromonas hydrophila) - Barbara, Shanta; Nursyirwani, Nursyirwani; Zulkifli, Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRAKThe research was conducted from November 2018 until May 2019. The purpose of this study was to determine the effect of T. hemprichii seagrass extract on the sensitivity of V. alginolyticus and A. hydrophila bacteria. The research used experimental method. Sensitivity test was carried out in the Marine Microbiology Laboratory of the Faculty of Fisheries and Marine, University of Riau. Based on the, sensitivity test positive control (K+) indicated hishest inhibitory zone diameter against V. alginolyticus andA. hydrophila39,57 mm and 42,11 mm, respretively. While there was not clear zone found in the negative control (K-). Extract of T. hemprichii had the hishest inhibitory zone against V. alginolyticus andA. hydrophila at a concentration of 100%, these were 2,45 mm and 2,58 mm, respectively. The lowest 10% indicated the lowest inhibitory zone against V. alginolyticus (0,65 mm) and A. hydrophila (0,38 mm).Key words: Extract, T. hemprichii,Sensitivity, V.alginolyticus and A. hydrophila,